CYK4 promotes antiparallel microtubule bundling by optimizing MKLP1 neck conformation. - Tim Davies; Noriyuki Kodera; Gabriele S Kaminski Schierle; Eric Rees; Miklos Erdelyi; Clemens F Kaminski; Toshio Ando; Masanori Mishima (PLoS Biology)
Centralspindlin, a constitutive 2:2 heterotetramer of MKLP1 (a kinesin-6) and the non-motor subunit CYK4, plays important roles in cytokinesis. It is crucial for the formation of central spindle microtubule bundle structure. Its accumulation at the central antiparallel overlap zone is key for recruitment and regulation of downstream cytokinesis factors and for stable anchoring of the plasma membrane at the midbody. Both MKLP1 and CYK4 are required for efficient microtubule bundling. However, the mechanism by which CYK4 contributes to this is unclear. Here we performed structural and functional analyses of centralspindlin using high-speed atomic force microscopy, Fӧrster resonance energy transfer analysis, and in vitro reconstitution. Our data reveal that CYK4 binds to a globular mass in the atypically long MKLP1 neck domain between the catalytic core and the coiled coil and thereby reconfigures the two motor domains in the MKLP1 dimer to be suitable for antiparallel microtubule bundling. Our work provides insights into the microtubule bundling during cytokinesis and into the working mechanisms of the kinesins with non-canonical neck structures.